If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = -4x + -6 Reorder the terms: 14 = -6 + -4x Solving 14 = -6 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 14 + 4x = -6 + -4x + 4x Combine like terms: -4x + 4x = 0 14 + 4x = -6 + 0 14 + 4x = -6 Add '-14' to each side of the equation. 14 + -14 + 4x = -6 + -14 Combine like terms: 14 + -14 = 0 0 + 4x = -6 + -14 4x = -6 + -14 Combine like terms: -6 + -14 = -20 4x = -20 Divide each side by '4'. x = -5 Simplifying x = -5
| 52-9x=2x+19 | | 4(z^2+11z-2)=-2z^2-7z+2 | | 9-45+8*4=778*x | | .33x+.67x=10 | | 100P=2400 | | 3=-6x-9 | | 3.5x-1.5x=18 | | .07x=1.4 | | 2w(-6-1)= | | 20x^2-27x=14 | | 2x+9=29-3x | | 58-7x=29x+18 | | t^2-t+1=0 | | 4x+5=6x-7 | | x^2-5xy+4y^2=0 | | 3x*(-5xy)=a | | 5x-4(x-7)=4+2x | | 99+m^2=0 | | 7x+8y-9z=6 | | 13x+13=62-4x | | 14x=-7 | | -35=5y | | -20=-5y | | 63=9y | | c^2=7c+18 | | -m^2-12=87 | | 4x+38=7x+20 | | X^2+4x^2+24x+24=4x^2+24x+36 | | 7+5a=8+2a | | 2x-3(x+6)=-4x(x-1) | | 7+7a+5a^2=8+2a+2a^2 | | 3y^2+10y=17y^2 |